iPS Cell Transplantation for Traumatic Spinal Cord Injury - Goulão, Miguel; C. Lepore, Angelo (Current Stem Cell Research & Therapy, 2016)
A large body of work has been published on transplantation of a wide range of neural stem and progenitor cell types derived from the developing and adult CNS, as well as from pluripotent embryonic stem cells, in models of traumatic spinal cord injury (SCI). However, many of these cell-based approaches present practical issues for clinical translation such as ethical cell derivation, generation of potentially large numbers of homogenously prepared cells, and immune rejection. With the advent of induced Pluripotent Stem (iPS) cell technology, many of these issues may potentially be overcome. To date, a number of studies have demonstrated integration, differentiation into mature CNS lineages, migration and long-term safety of iPS cell transplants in a variety of SCI models, as well as therapeutic benefits in some cases. Given the clinical potential of this advance in stem cell biology, we present a concise review of studies published to date involving iPS cell transplantation in animal models of SCI.
Keywords: Cell transplantation